Tell me your name and I will tell you where you are from: study of first names as an ethnic and religious heritage in an immigrant community. Franca: 1885-1945 - Maritan Gonçalves, José Victor [UNESP] (My University, 2022)
Microhistory was a path adopted as a theoretical and methodological proposal for the constitution of a social history. The reduced space and scale allow to know ways of interpersonal integration mapped from the nominative crossing of the documentation. In this sense, Ginzburg proposed the onomastic method, which uses the name as the guiding thread of the investigation. Starting from the quantitative analysis of the parish wedding seats of the Parish of Nossa Senhora da Conceição de Franca between the years 1885 and 1945, the study of Italian immigration flows will be applied for the analysis of the stock of names as intangible heritage and element of ethnic identity. The researched case reveals the social group to which the bearers of certain first names belong, as a reference of ethnicity demarcated by the family and religiosity.
Diga-me seu nome e te direi de onde és: estudo dos prenomes como um patrimônio étnico e religioso em uma comunidade imigrante. Franca: 1885-19451
Keywords: immigration; Italianity; nomination